The Development of Educational Practice Lecture Models to Prepare Adaptive and Innovative 21st-Century Primary School Teachers - Hastomo, Agung (Jurnal Prima Edukasia, 2024)
This research aims to develop a teaching model that combines problem-based educational methods with local culture and Technological Pedagogical Content Knowledge (TPACK) to train future primary school teachers who are adaptable and creative in the 21st century. The development model employed encompasses the subsequent phases: (1) preparatory stage, (2) prototype stage, and (3) assessment stage (Nieveen et al., 2016). The quality of the problem-based PK lecture model, which incorporates local culture and TPACK, is assessed based on its validity, practicality, and effectiveness (Francisca, 2017; Santi & Santosa, 2016). The development of the model includes the collaboration of two professionals, specifically curriculum experts and learning experts, together with the participation of five students who conduct practical knowledge (PK) activities in five elementary schools. The experimental trial consisted of 20 students who conducted instructional activities in 20 primary schools. The research and development findings indicate that the implementation of the PK lecture model has a feasibility rate of 91%, placing it in the outstanding category. Additionally, this learning model enhances students' competence and effectively improves learning outcomes in educational practices. Moreover, the model fosters a learning environment that integrates local culture and TPACK, equipping prospective elementary school teachers with adaptability and innovation skills for the 21st century.